P05.36 Skull base meningiomas: prognostic factors analysis for recurrence with multimodality treatment. (19th September 2018) - Pessina, F; Navarria, P; Clerici, E; Carta, G; Scorsetti, M; Bello, L
Abstract: Background: Meningioma is the most common primary intracranial tumor, accounting for approximately 15–30% of primary brain tumors. Skull base meningiomas, represent a subgroup of tumors in which a complete surgical removal is rarely achieved and the amount of surgical resection represents a crucial factor influencing the risk of recurrence. The role of adjuvant radiotherapy (RT) is still unclear and evidence is lacking. The aim of the present study was to evaluate prognostic factors influencing the local recurrence rate in a large series of grade I-II skull base meningiomas treated with surgery followed by RT in selected cases. Local toxicity, patients symptoms relief and local control rate were evaluated as well. Material and Methods: Newly diagnosed skull base meningiomas underwent surgery, were included. The extent of surgical resection (EOR) was defined according to Simpson criteria, and were dichotomized as gross total resection (GTR) and subtotal resection (STR). Adjuvant RT was considered in case of STR. Clinical outcome was evaluated by neurological examination and brain MRI performed every 6 months for the first year and yearly thereafter. The 30-days postoperative morbidity and mortality were recorded. Results: From January 2000 to December 2015, 142 patients were analyzed. The majority were female (69.1%), with a KPS ≥80 (95.8%), grade I meningioma(86.6%), and symptoms at diagnosis (92.3%). STR was performed in 69.7%, followed by adjuvant RT in 15%. Improvement or stability of neurological status was obtained in 78.9% of patients. The median follow-up time was 71 months (range 24–214 months). Local recurrence occurred in 43 (30.3%) patients at a median time of 32 months (range 6–199 months). No patients who underwent surgery plus adjuvant RT had local relapse. The median PFS was 172 months (95%CI 144–193 months), and the 2, 5, 10-year PFS were 87.9%(±2.8%), 78.2%(±3.8%) and 65.1%(±5.6%), respectively. The 2, 5, 10-year OS were (median not reached) 98.6% (±0.9%), 96.7% (±1.6%), and 94.4% (±2.7%), respectively. On univariate analysis factors identified as significantly impacting PFS were the EOR (p value<0.01), the combined treatment, surgery plus RT (p value<<0.01), and the meningioma grade (p value <0.01). The combined treatments was confirmed on multivariate too (p value <<0.01). Conclusion: Overall, our findings suggest that recurrence rates are influenced by WHO meningiomas grade, the extent of surgical resection, and the employ of adjuvant RT in not completely resected meningioma, regardless of tumor grade. Local control and durability of results suggest for a routine application of this approach in properly selected cases.